KESEJAHTERAAN BURUH ANAK DI PERKEBUNAN KELAPA SAWIT BATU NANTA BERDASARKAN UU NO. 4/1979 TENTANG KESEJAHTERAAN ANAK: Child Labor Welfare in Batu Nanta Palm Oil Plantations Based on Law No. 4/1979 on Child Welfare - Petra Gunawan; Wahyuni Retnowulandari (Jurnal Hukum PRIORIS, 2025)
This study aims to analyze the welfare of child laborers in palm oil plantations in Batu Nanta Village, Melawi Regency, West Kalimantan, with reference to Law No. 4 of 1979 concerning Child Welfare. The main focus of this study is to identification problem the causes of children working in oil palm plantations in the village and to what extent this phenomenon complies with the child protection provisions in the law. The method used is a normative approach with primary data collection through interviews and direct observation, as well as secondary data from literature and related documents. The research and conclusion findings indicate that poverty, low parental education levels, and local cultural norms that view child labor as part of the process of learning to live are the primary causes of children working. Additionally, the lack of legal oversight exacerbates the issue. This study demonstrates that these conditions contradict the principles of child welfare guaranteed by Law No. 4 of 1979, which emphasizes children's rights to live, grow, and develop in a healthy manner. In conclusion, synergistic efforts between the government, society, and families are needed to ensure child protection in accordance with applicable regulations.